Sebuah Tinjauan Pustaka: Pengaruh Kepemimpinan Efektif Dan Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dalam Organisasi Bisnis Di Era Digital - Suratno, Eddy (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This study aims to examine from an ontological aspect the influence of effective leadership and transformational leadership on employee performance in business organizations in the digital era. Literature review is the method used in this research where data collection was carried out using articles collected from 2018 to 2023. Reference articles were 31 scientific articles obtained from Google Scholar by searching